Correlation between poor palliative performance scale (pps) with or without brain lesion and overall survival in KFSH Dammam hospital during the year 2015 - Amani Alsayes, Aria Musailm, Dr. Ahmed Salah Ali, Muna Alshehabi, (Journal of Medical Biomedical and Applied Sciences, 2016)
Presence of brain lesions ,either primary or metastatic lesions ,may be the cause of cognitive function deterioration among cancer patients. This leads to further deterioration in his physical ability and tolerance for oral feeding. All these deteriorations are translated in low palliative performance status scores and subsequently poor outcome and less hope for more days for the patients to live as stated by the studies that correlate the survival with the palliative performance scale.